Trade, migration, and poverty reduction in the globalizing economy: The case of the Philippines - Yasuyuki Sawada; Jonna P. Estudillo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper investigates how the two types of globalization—i.e., integration of international trade and emigration—affected poverty reduction in the Philippines. Using the Family Income and Expenditure Surveys from 1985 to 2000, we found that both nontransfer and transfer incomes decreased poverty significantly but transfer income exerted greater impact. External openness reduced poverty significantly before the Asian currency crises but its impact had been reversed since. The effect of land reform in inducing transfer income from abroad was significant only in the 1990s. Yet, the ultra poor were bypassed in the land reform-credit-emigration-transfer nexus. – poverty ; globalization ; migration ; Millennium Development Goals
Keywords: F22; I32; O53; 330; Globalisierung; Auswanderung; Armut; Rücküberweisung (Migranten); Philippinen; Millennium Development Goals